The Future of Learning at the Workplace Is Augmented Reality. - Wild, Fridolin (Computer (00189162), 2016)
The next generation of performance support systems and tools for learning at the workplace are likely to be delivered in augmented reality (AR). Although there are many impressive prototypes and bespoke applications, interoperability has been neglected. To fix this, an IEEE Computer Society working group is creating a data format for the enrichment and exchange of AR learning content.